2012
DOI: 10.2337/db12-0214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Versus Resistance Exercise Without Caloric Restriction on Abdominal Fat, Intrahepatic Lipid, and Insulin Sensitivity in Obese Adolescent Boys

Abstract: The optimal exercise modality for reductions of abdominal obesity and risk factors for type 2 diabetes in youth is unknown. We examined the effects of aerobic exercise (AE) versus resistance exercise (RE) without caloric restriction on abdominal adiposity, ectopic fat, and insulin sensitivity and secretion in youth. Forty-five obese adolescent boys were randomly assigned to one of three 3-month interventions: AE, RE, or a nonexercising control. Abdominal fat was assessed by magnetic resonance imaging, and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
430
5
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(471 citation statements)
references
References 43 publications
26
430
5
10
Order By: Relevance
“…The DPP included 150 min/week of moderate-intensity exercise and showed beneficial effect on glycemia in those with prediabetes (1). Both resistance training and endurance exercise appear to have beneficial effects on waist circumference, insulin sensitivity, and thus diabetes risk (24,25). The preventative effects of exercise appear to extend to the prevention of gestational diabetes mellitus (GDM) as well (26).…”
Section: Physical Activity and Exercisementioning
confidence: 99%
“…The DPP included 150 min/week of moderate-intensity exercise and showed beneficial effect on glycemia in those with prediabetes (1). Both resistance training and endurance exercise appear to have beneficial effects on waist circumference, insulin sensitivity, and thus diabetes risk (24,25). The preventative effects of exercise appear to extend to the prevention of gestational diabetes mellitus (GDM) as well (26).…”
Section: Physical Activity and Exercisementioning
confidence: 99%
“…23,25,28,40,51,53,57,58 Sensitivity analysis removing these 9 effects decreased the mean effect of exercise on fasting insulin in children and adolescents from .001) for the remaining 24 effects. When examining IR, 3 effects from 2 studies outside of the 95% CI were identified by using the forest plot to identify potential outliers.…”
Section: Effect Of Potential Outliersmentioning
confidence: 99%
“…Moreover, despite performing double the training load of the aerobic alone or PRT alone groups, aerobic exercise combined with PRT led to a non-significant reduction in liver fat. A superior hepatic benefit of aerobic exercise training was also demonstrated in obese adolescent girls [12]; however, comparable reductions between aerobic and resistance training have been observed in NAFLD patients with type 2 diabetes [5] and in obese adolescent boys [13].…”
Section: Progressive Resistance Trainingmentioning
confidence: 98%
“…To date, there is sparse evidence for the efficacy of PRT as per these guidelines for liver fat reduction. Of the nine studies employing PRT in isolation, five observed a significant reduction in liver fat [5,13,[17][18][19], three of which conformed with the abovementioned guidelines [5,13,18], while four showed no benefit [12,[20][21][22] with discrepancies in outcomes likely due to the large heterogeneity in study design. These differences include the use of circuit-based training (which has a concurrent 'aerobic' exercise stimulus) [19,22], the use of home-based prescription [17], and variation in training intensities and study populations, all of which combined limit the ability to generalize findings and draw practical conclusions.…”
Section: Progressive Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation